On the Dual Basis of Projective Semimodules and Its Applications - Deore, R. P.; Patil, K. B. (Sarajevo Journal of Mathematics, 2024)
The dual basis lemma for projective semimodule over a semiring is proved. We show under which conditions the two categories cs mod-R and S-cs mod of cancellative semimodules are equivalent and how these equivalences are realized.